‘In the Mills, We Are Not So Far from God and Nature’: Industrialization and Spirituality in Nineteenth-Century New England - Weiss, Jane (Journal for the study of religion, nature and culture, 2011)
Beginning in the 1820s, industrialization wrought profound and violent disruptions in the culture of the northeastern United States. Lowell, Massachusetts, grew from a rural village of 1500 people in 1820 to a manufacturing city of 33,000 in 1850. Newcomers found crowds, buildings, and noise spiritually assaultive: one yearned ‘to find myself alone for a brief space, that I might hold communion with my own heart undisturbed’. In response to these yearnings, Lowell’s developers and laborers eschewed artful fabrications of pastoral countryside or wilderness. Instead, they incorporated greenery into canals, factories, and streets, weaving sacred space into industrial urbanism. Writings by Lowell’s ‘mill girls’ detail the spiritual rewards-some actively sought, some serendipitous-of their lives in the city. Although the hopes of the city’s founders and workers that balance could be achieved between mass production of material goods and harmony with nature were not fully realized, the gardens, green spaces, and human ecology of Lowell provide models for sustainable and spiritually fruitful industrialization and urbanism in the twenty-first century.